2019
DOI: 10.1111/jfs.12746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant level and protein oxidation of rainbow trout (Oncorhynchus mykiss) fillets during rigor and post‐rigor

Abstract: In this study, the relationship between stunning techniques and protein oxidation which are accepted as the main cause of food spoilage was investigated. For this purpose, the antioxidant status, in vivo myofibrillary protein (MP) oxidation and sensitivity, and postmortem oxidation (inducted with hydroxyl radical system) of rainbow trout (Oncorhynchus mykiss) fillets killed by hitting to head (T1), neck crushing (T2), and convulsion (T3) methods, were investigated. Statistically significant differences (p < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…This situation is attributed to impaired antioxidant enzyme activity increasing the likelihood of oxidation of disulfide bonds and thereby reducing the concentration of -SH. 15 However, direct oxidation of protein side chains has been reported to be responsible only for carbonylation in meat proteins. 45 Cheng et al 46 reported protein oxidation in terms of carbonyl content in sarcoplasmic and MPs of dried chopped pork slices and conversion of -SH groups into S S groups during thermal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is attributed to impaired antioxidant enzyme activity increasing the likelihood of oxidation of disulfide bonds and thereby reducing the concentration of -SH. 15 However, direct oxidation of protein side chains has been reported to be responsible only for carbonylation in meat proteins. 45 Cheng et al 46 reported protein oxidation in terms of carbonyl content in sarcoplasmic and MPs of dried chopped pork slices and conversion of -SH groups into S S groups during thermal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The fish had previously been killed using a common killing technique described by Işık et al 15 The analysis was conducted taking into account the period in which rigor would occur. The glycogen level was determined spectrophotometrically as 620 nm within the first 6 h using a commercial kit (Abcam, Glycogen Assay Kit, www.soci.org G Alak et al…”
Section: Water-holding Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemically, there is an increment in the toxic mechanism of movement because of the affinity between metals, so the sulfhydryl groups (–SH) attack heavy metal‐containing cations or molecules. The resulting metal‐SH bond may affect the enzyme, causing loss of its catalytic activity (Isık et al, 2020; Marins et al, 2019). When large numbers of ROS are stimulated, oxidative stress can be triggered as a harmful biological reply.…”
Section: Discussionmentioning
confidence: 99%
“…Protein oxidation has been deemed as a major contributor to the deterioration of fish (Zhang, Shan, et al, 2020).Deterioration of fish quality may occur under degradation, denaturation, or aggregation of proteins during transportation and storage. Several studies have reported the changes in the structure and physicochemical properties of myofibrillar protein during storage, suggesting that protein denaturation is a major contributor of shelf-life decline, nutrient loss, and structural changes in fish (Alak et al, 2021;Isık et al, 2020). Protein oxidation is a complicated phenomenon that involves amino acid residues, buried hydrophobic exposure, and protein unfolding upon heating (Dericioglu at al., 2019).…”
mentioning
confidence: 99%